Profile of hospitalizations for neoplasms in the Brazilian Unified Health System: a time-series study - Analy da Silva Machado; Anaely da Silva Machado; Dirce Bellezi Guilhem (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE Describe the profile of hospitalizations for cancer diagnosis in Brazil from 2008 to 2018 at Unified Health System (SUS). METHODS Time series study of hospitalization rate for malignant neoplasms at SUS. Data were extracted from the Hospital Information System of DataSUS. The trend was estimated using generalized linear regression, applying the Prais-Winsten estimation procedure. RESULTS From 2008 to 2018, the hospitalization rate for malignant neoplasms showed an increasing trend at SUS, with an annual variation of 10.7% (p < 0.001; CI = 9.4-11.7). An increasing trend of hospitalizations in all regions of Brazil was observed, except in the Northern region, which remained unchanged. The Northeastern region presented the highest annual variation (13.5%; p < 0.001), whereas the Southern and Southeastern regions had the highest hospitalization rates per 100,000 inhabitants, resulting in 506 and 325 hospitalizations, respectively. We observed a significant increasing trend in hospitalizations of children aged 0 to 9 years (annual variation = 10.9%; p < 0.001); young people, 10 and 19 years (annual variation = 6.9%; p < 0.001); and older adults; over 60 years (annual variation = 7.9%; p < 0.001). Among women, hospitalizations occurred mainly due to malignant neoplasm of the breast (annual variation = 13.2%; p < 0.001); and among men, malignant neoplasm of the prostate (annual variation = 4.7%; p < 0.001). CONCLUSION Hospitalizations for malignant neoplasms showed an increasing trend, in line with the increased incidence of cancer, in particular, the most frequent neoplasms between men and women. Although the Northeastern region showed the highest variation in the period, the Southern and Southeastern regions had the highest hospitalization rates in the country. We also observed an increase in hospitalizations among the young (between 0 and 19 years old) and older adults (over 60 years) population. Hospitalizations for neoplasm of the cervix in women, although still the third cause of hospitalizations, showed decreasing behavior.